Implementasi Pencatatan Transaksi Keuangan dalam Pengelolaan Budidaya Kerang Hijau (Sea Farming) pada Koperasi ISM Karya Sinar Bahari, Desa Tanggul Jaya, Kelurahan Banten, Kecamatan Kasemen, Kota Serang, Provinsi Banten - Pratama, Ginanjar Dwi; Ariesta, Priscilla Gareen; Simanjuntak, Mei Sunday; Prayudharikanto, Didiet Hardi; Zulfitra, Zulfitra; Sewaka, Sewaka (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This community service is entitled Implementation of Financial Transaction Recording in the Management of Green Mussel Cultivation (Sea Farming) at the ISM Karya Sinar Bahari Cooperative, Tanggul Jaya Village, Banten Sub-district, Kasemen District, Serang City, Banten Province. The method used in this study is the survey method and direct delivery of materials as well as simulations and discussions on the implementation of financial transaction recording. The conclusion of this community service is that assistance will be provided in the implementation of neat and easy financial transaction recording when checking financial data for a certain period.